Efficacy of Aqueous Extracts of some Libyan Medicinal Plants Against Sclerotinia sclerotiorum In Vitro - Hypa, Nisreen M.; El-Gali, Zahra I. (Al-Mukhtar Journal of Sciences, 2022)
The study was conducted to test the effect of aqueous extracts of the leaves of ten medicinal plants growing naturally in Al-Jabal Al-Akhdar region – northeast Libya, which include: Alhagi (Alhagi camelrum), Mugwort (Artimesia herba-alba), Everlasting (Helichrysum stoechas), Chamomile (Anthemis noblis), Stinkweed (Peganum harmala), Nettle (Urtica dioica), Rosemary (Rosmarinus officinalis), Rue (Ruta graveolens), Geranium (Pelargonium graveolens) and Castor (Risinus communis) using poisoned plate method in PSA medium against Sclerotinia sclerotiorum caused seeds’ rot and seedlings damping-off. The results showed a significant difference in inhibition effectiveness in all extracts against the tested fungus. Among all plants, H. stoechas was the most effective (88.4%), followed by U. dioica (79.1%), then P. harmala (78.3%). Chemical detections showed that the extracts of H. stoechas, P. harmala, and U. dioica contained some antioxidants: phenols, flavonoids, and tannins. Based on these results application of plant extracts can be considered a beneficial strategy for controlling fungal plant diseases.